THE INFLUENCE OF LOCAL AND FOREIGN ENDORSERS’ CREDIBILITY AND ATTRACTIVENESS IN COSMETICS ADVERTISEMENTS ON CONSUMER PERCEPTIONS AND PURCHASE DECISIONS - Mu’min Gozali; Achmad Fudholi; Satibi Satibi (Faculty of Pharmacy, Universitas Gadjah Mada)
Endorser used on product advertising is ordinary thing on marketing. Developments in the flow of informationand technology have caused consumers to be increasingly selective in their choice of products. This fact hasstimulated companies to be more sensitive to consumer demand. Advertising is one of the promotional activitiesused as a medium for conveying a message to shape consumers’ attitudes. This research was conducted to measurethe influence of local and foreign endorsers’ credibility and attractiveness on consumer perceptions and purchase decisions, and to look into the difference between the use of local endorsers and the use of foreign endorsers in their influence on consumer perceptions and purchase decisions. This was an experimental research carried out in two phases, i.e. exploratory analysis and confirmatory analysis using a cross-sectional approach. The researchinstruments employed were samples of advertisements and questionnaires. The research subjects comprised130 respondents each for local and foreign endorsers. The data were analyzed using simple regression and anindependent t-test with SPSS 11.5 for windows. The research results showed that the ability of local endorsers’credibility and attractiveness to predict the consumer perceptions variable was 16.4%, their ability to predict consumerpurchase decisions was 11.3%. The ability of foreign endorsers’ credibility and attractiveness to predict the consumerperceptions variable was 30.1%, and their ability predict consumer purchase decisions was 37.4%. After a comparison was made using an independent sample t-test, it was found that consumer perceptions of advertisements with localendorsers were lower than consumer perceptions of advertisements with foreign endorsers, and consumer purchasedecisions on products advertised with local endorsers were fewer than consumer purchase decisions on productsadvertised with foreign endorsers. Keywords : advertisements, endorsers’ credibility, endorsers’ attractiveness